A Knowledge Management Challenges for Start-Ups: A Framework Proposal - Theocharis Stylianos Spyropoulos (IJEBD (International Journal of Entrepreneurship and Business Development), 2020)
The study reviews the knowledge management challenges faced by innovative start-ups founders and entrepreneurs. Knowledge management is critical for innovation, since both organisations and individuals face very specific needs: collection of a wide variety of information and data, such as market data and technical information, and a wide range of transformation of these data into applicable knowledge, in the forms of required product specifications, business model, and business strategy. In addition, the business financing and investment ecosystem (especially Banks & Venture Capitals) uses a traditional “business plan” approach for evaluating innovation companies. Furthermore, a wide range of tools (databases, online information, Collaboration Systems, Business Intelligence Systems, ERP & CRM Systems) enable information flow and supports decision making process. To this respect, both academic literature and business experience highlight the need to improve Knowledge Management process both for individuals and organisations engaged in Innovation management. The proposed framework provides academics, entrepreneurs and venture capital companies a new approach for identifying critical success factors knowledge management and further improves decision making in a changing and challenging business environment. Finally the study highlights key areas for further research.